AB0054 A rapid and marked reduction of serum vegf via blocking il-6 signal was associated with early clinical responses to tocilizumab and infliximab in patients with rheumatoid arthritis. (23rd January 2014) - Hashizume, M.; Nishina, N.; Kikuchi, J.; Yoshimoto, K.; Kameda, H.; Takeuchi, T.
Abstract : Background: Accumulating evidence now suggests that major clinical response at three months after a given treatment may be one of the potential predictors for clinical remission at one year of treatment, supporting the concept of Treat to Target (T2T) strategy. Recently we have reported that the profound suppression of IL-6 by anti-TNF-α antibody, infliximab (IFX) was associated with achievement of clinical remission at one year, suggesting the inevitable role of IL-6 on clinical response[1 ]. Objectives: We explored whether serum levels of biomarkers including IL-6 can be the predictors for early clinical response not only to treatment involving the inhibition of IL-6 signaling, but also to TNF-α targeted treatment. Methods: Consecutive RA patients who started anti-IL-6 receptor antibody, tocilizumab (TCZ) or IFX in Keio hospital and obtained the informed consent were included in this study. Patients with IFX who sustained doses at 3 mg/kg every 8 weeks and kept its efficacy until 52 weeks were selected. Serum levels of 12 biomarkers were measured at week 0 and 4 for TCZ and at week 0 and 6 for IFX. Trends of biomarkers were evaluated by Wilcoxon test. Associations between change ratio of biomarkers at week 4 or 6 from baseline and change ratio of DAS28-CRP/SDAI/CDAI at 12 weeks for TCZ and 14 weeks for IFX from baseline were evaluated by Spearman correlation. Results: Each group of characteristics at baseline was no significantly different. The following biomarkers had significantly changed from baseline to 4 or 6 weeks after TCZ or IFX treatment (table ). Change ratio of serum VEGF from baseline at week 4 or 6 was significantly correlated to change ratio of DAS28-CRP (R=0.37, p=0.0031 in TCZ, R=0.55, p=0.0422 in IFX) and SDAI (R=0.49, p<0.0001 in TCZ), similar to its correlation with CDAI (R=0.45, p=0.0003 in TCZ). The reduction of IL-6 from baseline at week 6 in IFX showed good agreement with VEGF (R=0.61, p=0.0053) and sICAM-1, (R=0.49, p=0.0435). Image/graph: Conclusions: The rapid suppression of VEGF via direct/indirect inhibition of IL-6 by both TCZ and IFX results in better clinical response and may offer complementary information about rapid quiescence of underlying biological disease pathways. References: Takeuchi T, et al. Ann Rheum Dis 2012;71:1583-1585. Disclosure of Interest: M. Hashizume Employee of: Chugai Pharmaceutical Co., Ltd, N. Nishina: None Declared, J. Kikuchi Consultant for: Pfizer Japan Inc., K. Yoshimoto: None Declared, H. Kameda: None Declared, T. Takeuchi Grant/research support from: Abbott Japan Co., Ltd., Astellas Pharma Inc., Bristol-Myers Squibb K.K., Chugai Pharmaceutical Co., Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Nippon Shinyaku Co., Ltd., Otsuka Pharmaceutical Co., Ltd., Pfizer Japan Inc., Sanofi-Aventis K.K., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., and Teijin Pharma Ltd., Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co. and Asahi Kasei Medical Co., Ltd.